PCR Based Diagnosis of Eimeria tenella Infection in Broiler Chicken - Patra, Gautam; Ali, M. Ayub; Chanu, Kh. Victoria; Jonathan, L.; Joy, L.K.; Prava, M.; Ravindran, R.; Das, G.; Devi, L. Inaotombi (International Journal of Poultry Science, 2010)
The present investigation was undertaken to evaluate histo-pathological, haemotological and biochemical changes in broiler chicken naturally infected with Eimeria tenella. A Polymerase Chain Reaction (PCR) based assay was also done for the detection, identification and differentiation of pathogenic species of Eimeria in poultry. Post mortem examination revealed petechial haemorrhages, oedema, necrosis and sloughing of caecal epithelium. Histopathological evidence showed leakage of blood, oedema and necrosis. Haemotological studies revealed that coccidial infection caused significant decrease in the value of haemoglobin and Packed Cell Volume (PCV). The value of Mean Corpuscular Volume (MCV) and Mean Corpuscular Haemoglobin Concentration (MCHC) revealed that caecal coccidiosis resulted in macrocytic hypochromic anaemia. Biochemical serum analysis of coccidial infected chicken showed a significant increase in level of glucose, Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST) while there was a significant decrease in the level of alkaline phosphatase (SAP) and cholesterol. In PCR using specific primers for E. tenella only the ITS 1 regions of ribosomal DNA (rDNA) could be amplified.